Use of parenteral L-Carnitine in breed Holstein cows - Zabala Mendoza, Alcides; Correa Cardona, Héctor Jairo; Giraldo Mejía, Ángel María (Spei Domus, 2021)
Introduction: Carnitine is key in the proper metabolism of lipids, so its deficiency can trigger metabolic and productive problems during peripartum, for this reason, the objective of this study is evaluated the parenteral application of various doses of L-carnitine to cows during the peripartum;Methodology: Each treatment consisted of six Holstein cows between second and sixth birth to Holstein cows of high production, grazing kikuyu grass (Cenchrus clandestinus [Hochst. ex Chiov.] Morrone) and supplemented with a concentrate food 0, 5, 10 and 15 grams of L-carnitine in solution were applied via intramuscular every 5 days from day 270 of gestation to day 15 postpartum on dry matter intake (DMI), energy balance (EB), milk yield (MY) and milk content of fat (MF) and protein (MP). The DMI was estimated using the indicator technique. MY, MF and MP were measured on days 5, 10, 15 and 20 of lactation. On day 270 of gestation and on days 10 and 20 postpartum the EB of each cow was calculated.Results: The results of these measurements are analyzed in a time-divided plot design. Conclusions: The treatments do not affect DMI, MY, MP, MF and EB (p> 0.05), under the experimental conditions described in this work, parenteral L-carnitine has no effect on milk production, composition and EB.
Keywords: dry matter intake; energy balance; milk composition; milk production; transition